2014
DOI: 10.1038/cgt.2014.42
|View full text |Cite
|
Sign up to set email alerts
|

Cancer stem-like cells from head and neck cancers are chemosensitized by the Wnt antagonist, sFRP4, by inducing apoptosis, decreasing stemness, drug resistance and epithelial to mesenchymal transition

Abstract: Cancer stem cells (CSCs) of head and neck squamous cell carcinoma (HNSCC) are defined by high self-renewal and drug refractory potential. Involvement of Wnt/β-catenin signaling has been implicated in rapidly cycling cells such as CSCs, and inhibition of the Wnt/β-catenin pathway is a novel approach to target CSCs from HNSCC. In this study, we found that an antagonist of FrzB/Wnt, the secreted frizzled-related protein 4 (sFRP4), inhibited the growth of CSCs from two HNSCC cell lines, Hep2 and KB. We enriched th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
78
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 43 publications
5
78
0
Order By: Relevance
“…CSCs are niche forming cells enriched with growth factors, and growing them in serum-free conditions containing growth factors, such as epidermal growth factor (EGF) and basic fibroblast growth factor (bFGF), maintains the undifferentiated stem cell state and induces the proliferation of self-renewing, unipotent CSCs from parental cell lines [4, 25, 26]. CSCs are characterised by specific surface markers such as CD133 + /CXCR4 + , CD24 + /CD44 + , CD24 + /CD44 + /ESA + , c-Met + /CD44 + , and ALDH1 + /CD133 + in pancreatic cancer [27, 28]; CD24 −/low /CD44 + in breast cancer; CD44 + in colon/ gastric/ head and neck/ovarian cancer; CD34 + /CD38 − in leukaemia cells; CD13/CD45/CD90 in liver cancer; CD117/CD90/EpCAM in lung cancer; CD20/CD166/Nestin in melanoma cancer; and CD133 + /ABCG2 + in Glioblastoma Multiforme [29, 30]. CSCs also express various markers such as CXCR4/ ESA and Nestin [27].…”
Section: Cancer Stem Cellsmentioning
confidence: 99%
“…CSCs are niche forming cells enriched with growth factors, and growing them in serum-free conditions containing growth factors, such as epidermal growth factor (EGF) and basic fibroblast growth factor (bFGF), maintains the undifferentiated stem cell state and induces the proliferation of self-renewing, unipotent CSCs from parental cell lines [4, 25, 26]. CSCs are characterised by specific surface markers such as CD133 + /CXCR4 + , CD24 + /CD44 + , CD24 + /CD44 + /ESA + , c-Met + /CD44 + , and ALDH1 + /CD133 + in pancreatic cancer [27, 28]; CD24 −/low /CD44 + in breast cancer; CD44 + in colon/ gastric/ head and neck/ovarian cancer; CD34 + /CD38 − in leukaemia cells; CD13/CD45/CD90 in liver cancer; CD117/CD90/EpCAM in lung cancer; CD20/CD166/Nestin in melanoma cancer; and CD133 + /ABCG2 + in Glioblastoma Multiforme [29, 30]. CSCs also express various markers such as CXCR4/ ESA and Nestin [27].…”
Section: Cancer Stem Cellsmentioning
confidence: 99%
“…In cervical cancer, ALDH1-positive cells, like other solid tumors, are known to be more tumorigenic than negative ones, and we used ALDH1 as a marker of cervical CSCs (25)(26)(27)(28)(29)(30)(31)(32)(33)(34). First, using the cervical cancer cell line CaSki we confirmed that the expression of PAI-1 was significantly increased by changing coatings of culture plates as described (35), especially collagen IV-coating, confirmed by enzyme-linked immunosorbent assay (ELISA).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Snail was reported to trigger epithelial-mesenchymaltransition in tumor progression (37).SFRP4, another specifically Wnt antagonist, by inducing apoptosis, decreasing epithelial to mesenchymaltransion in head and neck cancer (38).…”
Section: Discussionmentioning
confidence: 99%